PENGARUH LINGKUNGAN KERJA DAN KOMPETENSI PEGAWAI TERHADAP KINERJA PEGAWAI BADAN PERENCANAAN DAN PEMBANGUNAN DAERAH (BAPPEDA) KABUPATEN LAMPUNG TENGAH - Septi Astinasari (Universitas Muhammadiyah Metro, 2020)
The aim of this research were to determine the Effect of Work Environment and Employee Competence on Employee Performance. This type of research using quantitative approaches and data collection techniques using questionnaires and observations. The population in this study were employees who worked at Staffing and Regional Planning and Development Agencyin Central Lampung Regency and were sampled by purposive sampling using the Slovin formula to 39 respondents. Data analysis using multiple linear regression analysis with the help of SPSS 21. Findings signify that: (1) Is work environment significant to employee performance? (2) is competence significant for employee performance? (3) Does work environment and competence have a significant effect on employee performance?